2019
DOI: 10.1155/2019/2328054
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Inadequate Bowel Preparation Using Total and Segmental Colon Transit Time in Patients with Chronic Constipation: Some Different Outcomes

Abstract: Aims Radio-opaque markers have been widely used in the study of colon motility in patients with chronic functional constipation (FC). Here, we evaluate the relationship between the colon transit time (CTT) and the Boston Bowel Preparation Scale (BBPS) to determine whether CTT is a sufficient predictor of bowel preparation in patients with chronic functional constipation. Methods A total of fifty-six patients with constipation and fifty-two healthy controls (HC) were enrolled in this study. All subjects underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…Two previous studies have suggested that slow-transit constipation may be a risk factor for inadequate bowel preparation 7,30. In the subgroup of patients undergoing ROM colonic transit testing, we found a similar association.…”
Section: Discussionsupporting
confidence: 85%
“…Two previous studies have suggested that slow-transit constipation may be a risk factor for inadequate bowel preparation 7,30. In the subgroup of patients undergoing ROM colonic transit testing, we found a similar association.…”
Section: Discussionsupporting
confidence: 85%
“…Chronic constipation patients have dysfunction for colon motility and become an independent risk factor of inadequate bowel preparation before the colonoscopy (Dik et al, 2015;Mahmood et al, 2018). Further study confirmed that prolonged colon transit time was independently associated with inadequate bowel preparation in constipation patients (Zhai et al, 2019). Lee et al (2017)found that infrequent bowel movements (<3/week) were an independent risk factor of poor bowel preparation.…”
Section: Discussionmentioning
confidence: 89%
“…A few studies prove that bowel symptoms such as type 1 or 2 of the Bristol stool form scale (BSFS), starting-to-defecation interval ≥4 h, and infrequent bowel movement (<3/week) could predict IBP ( Lee et al, 2017 ; Guo et al, 2020 ). Some studies found that the colon transit time test represents a useful mean for predicting IBP before colonoscopy ( Park et al, 2015 ; Zhai et al, 2019 ). These evidences may be valuable for formulating individualized BP strategies in constipated patients until verified by a large cohort study.…”
Section: Discussionmentioning
confidence: 99%